Fear of venepuncture as a barrier to testing for blood-borne infection and use of an oral fluid test as an alternative to venepuncture in a genitourinary medicine clinic. Issue 1 (10th November 2006) - McClean, H L; Taylor, A J; Mortimer, A M
Abstract : Objective: A survey of 505 consecutive patients attending a UK genitourinary medicine clinic (GUM) included a psychometric tool to compute a fear of venepuncture (FOV) score, responses to the offer of venepuncture and to alternative testing. Method: An oral fluid test (OFT) was available to test for blood-borne infection (BBI). Completed fear scores were provided by 299 (59%) patients routinely offered venepuncture, of whom 72 (24%) who did not have venepuncture had higher fear scores compared with 227 (76%) who had venepuncture (p<0.001). Results: Both FOV and female sex were independent predictors of not having venepuncture. Conclusions:: FOV is an important barrier to uptake of venepuncture. FOV maynot always be recognised by health carers. OFT is an acceptable alternative test for some patients with needle aversion who decline venepuncture.